Identifikasi Jenis Tanaman Bambu ( Bambusa sp) di Hutan Bambu Alu Kecamatan Alu Kabupaten Polewali Mandar - Salwah; Idris, Andi Irmayanti; Indhasari, Fitri (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2023)
Bamboo is an abundant natural resource with high diversity. In general, bamboo is very easy to find in society because sufficient resources are available in nature. The use of bamboo also varies based on the type of bamboo in the Alu bamboo forest. The aim of this research is to identify the type of plant (Bambusa sp) found in the Alu bamboo forest, Alu District, Polewali Mandar Regency. This research uses an exploratory descriptive research method, namely research that describes what a situation is like. And the method variable is the survey method used with the technique of identifying the types of bamboo plants in the Alu bamboo forest. Data collection was carried out by recording bamboo morphology starting from bamboo shoots, stems, branches, stems and leaves. The genus and species of bamboo found were identified, secondary data was obtained from consumer interviews and the creation of a herbarium. There are 3 types of bamboo plants found in the Alu bamboo forest, namely betung bamboo (Degantocamus asper), apus bamboo (Gigantochloa apus), parring bamboo (Gigantochloa atter). The types that are widely used are parring bamboo by 62 people, apus bamboo by 37 people. 36 people, Betung bamboo, these types of bamboo are used as building materials, handicrafts, for sale, household equipment and firewood. Keywords: Identification, types of bamboo, use of bamboo.